一种定向石墨材料及其制备方法 (2023)
本发明公开了一种定向石墨材料及其制备方法，包括以下步骤：S1、按中间相沥青含量占比12-22wt％，热塑性树脂占比4-5.5wt％，天然石墨占比72-82wt％的配比，加热搅拌混合均匀，冷却到100-150℃；S2、步骤S1得到的混合物再加入占比为0.5-2wt％的氧化石墨烯，搅拌混合均匀冷却至室温，粉碎成混合粉料；S3、将混合粉料热模压成型，再放入高温石墨化炉烧结冷却得到石墨材料。加入聚酰亚胺和氧化石墨烯，利用聚酰亚胺树脂残炭率高、氧化石墨烯含有丰富官能团的特点。通过添加少量的氧化石墨烯为聚酰亚胺树脂、中间相沥青和天然石墨之间提供纳米粒子桥接作用，增加分子界面结合力，进一步改善材料整体的强度和导热性能。 The invention discloses an oriented graphite material and a preparation method thereof. The preparation method comprises the following steps: S1, heating, stirring and uniformly mixing 12-22 wt% of mesophase pitch, 4-5.5 wt% of thermoplastic resin and 72-82 wt% of natural graphite, and cooling to 100-150 DEG C; S2, adding 0.5-2 wt% of graphene oxide into a mixture obtained in step S1, stirring and uniformly mixing, cooling to room temperature, and crushing into mixed powder; and S3, carrying out hot compression molding on the mixed powder, sintering in a high-temperature graphitization furnace, and cooling to obtain the graphite material. Polyimide and graphene oxide are added, and the characteristics that p